2009
DOI: 10.1080/17450390903020422
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phytate and phytase on proteolytic digestion and growth regulation of broilers

Abstract: This study was designed to investigate the effect of dietary phytate and phytase on proteolytic digestion and growth signalling in the gastrointestinal tract of broilers. Diets containing phytate phosphorus (2.2 or 4.4 g/kg) with phytase dose rates of 0, 500, or 1,000 FTU/kg were fed to 504 female Cobb chicks for three weeks. Diets containing high phytate reduced the activity of pepsin and trypsin, whereas the inclusion of microbial phytase increased the activity of pepsin, H(+)K(+)-ATPase, trypsin and alanyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…The addition of phytase to pig and poultry diets tends to disproportionately improve the ileal recovery of threonine, serine, proline, aspartic acid, glycine and cysteine compared with the more recalcitrant amino acids methionine, arginine, glutamic acid and lysine (Cowieson and Bedford 2009). This is partly due to a reduction, with phytase addition, in ileal endogenous amino acid flow (Cowieson and Ravindran 2007) and partly due to altered absorptive function (Liu et al 2009). The separate feeding of Ca in the present study resulted in an improvement in ileal amino acid digestibility of 8% (comparing the 2.5 g/kg diet with the 10 g/kg diet).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of phytase to pig and poultry diets tends to disproportionately improve the ileal recovery of threonine, serine, proline, aspartic acid, glycine and cysteine compared with the more recalcitrant amino acids methionine, arginine, glutamic acid and lysine (Cowieson and Bedford 2009). This is partly due to a reduction, with phytase addition, in ileal endogenous amino acid flow (Cowieson and Ravindran 2007) and partly due to altered absorptive function (Liu et al 2009). The separate feeding of Ca in the present study resulted in an improvement in ileal amino acid digestibility of 8% (comparing the 2.5 g/kg diet with the 10 g/kg diet).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Knuckles et al (1989) reported a 9 to 14% reduction in pepsin digestion of casein and bovine serum albumin in vitro due to addition of phytic acid to the incubation media, whereas Vaintraub and Bulmaga (1991) reported a 60 to 92% reduction in pepsin digestion of casein, hemoglobin, bovine serum albumin and soybean protein in vitro due to addition of phytic acid to the incubation media. Furthermore, Liu et al (2009) reported a 6.3% reduction in the activity of pepsin in the proventriculus of broiler chickens due to dietary phytic acid, whereas observed reduced activity of pepsin in piglets by 46% due to addition of phytic acid to a phytic acid-free diet.…”
Section: Effect Of Phytic Acid On Endogenous Losses Of Mineralsmentioning
confidence: 99%
“…Phytic acid has been reported to reduce the activity of porcine pancreatic lipase in vitro (Knuckles et al 1989) and pancreatic lipase activity in the small intestine of broilers (Liu et al 2009), implying that the reduced fat digestibility by phytic acid could partly be a result of reduced activity of lipase. Phytic acid could also reduce fat digestibility and absorption by binding bile acids via divalent cations such as calcium to form insoluble phytic acid-mineral-bile acids complexes, thereby reducing fat digestion and absorption, and bile acids re-absorption.…”
Section: Effect Of Phytic Acid On Energy Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations